Organisasi Bundo Kanduang dan Pendidikan Karakter Generasi Muda di Masa Pandemi - Yolanda Anggun Sari; Ranti Nazmi; Azwar Azwar (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
This study aims to look at the involvement of the Bundo Kanduang Organization in implementing character education for the younger generation in Nagari Mungka, Lima Puluh Kota District. This is motivated by the decline in character that occurred during the Covid-19 pandemic which was seen from the excessive use of gadgets by the younger generation. The research method is qualitative with a descriptive approach with research subjects: the management of the Bundo Kanduang organization and the younger generation in Nagari Mungka. The results of this study are that there is the involvement of the Bundo Kanduang organization in implementing character education for the younger generation through various programs, such as: wirid at mosques and in residents' homes, socialization of the dangers of drugs and education on Minang customs and culture to Rang Mudo jo Puti Bungsu. The limitation of this research is that it has not seen the role of the Nagari government in increasing the creativity of the younger generation.